2018
DOI: 10.1364/ao.57.003738
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of optical properties of photonic crystal fibers infiltrated with carbon tetrachloride for supercontinuum generation with subnanojoule femtosecond pulses

Abstract: A photonic crystal fiber (PCF) made of fused silica glass, infiltrated with carbon tetrachloride (CCl), is proposed as a new source of supercontinuum (SC) light. Guiding properties in terms of effective refractive index, attenuation, and dispersion of the fundamental mode are studied numerically. As a result, two optimized structures are selected and verified against SC generation in detail. The dispersion characteristic of the first structure has the zero-dispersion wavelength at 1.252 μm, while the dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…Recently, use of liquid-filled PCFs has been received more attention because it overcomes the disadvantages of liquids capillary approach. The obtained results indicated that it is possible to shift the ZDW and match it with a pump wavelength of the high-power commercial laser, as well as obtaining allnormal and flat dispersion regime in the expected spectra (Van et al 2018a;Maji and Chaudhuri 2014;Ding et al 2018). Due to the higher nonlinear refractive index of selected liquids (Ding et al 2018;Kedenburg et al 2014), it is possible to achieve the broadband, coherent SC spectrum either in a few centimeters long liquid-core fiber sample, or with a lower peak power (Van et al 2020).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, use of liquid-filled PCFs has been received more attention because it overcomes the disadvantages of liquids capillary approach. The obtained results indicated that it is possible to shift the ZDW and match it with a pump wavelength of the high-power commercial laser, as well as obtaining allnormal and flat dispersion regime in the expected spectra (Van et al 2018a;Maji and Chaudhuri 2014;Ding et al 2018). Due to the higher nonlinear refractive index of selected liquids (Ding et al 2018;Kedenburg et al 2014), it is possible to achieve the broadband, coherent SC spectrum either in a few centimeters long liquid-core fiber sample, or with a lower peak power (Van et al 2020).…”
Section: Introductionmentioning
confidence: 87%
“…An alternative solution is liquid-infiltrated optical fibers, as demonstrated in previous research (Zhang et al 2006;Fanjoux et al 2017; Van et al 2018a;Maji and Chaudhuri 2014;Pniewski et al 2016;Ding et al 2018;Lanh et al 2019; Van et al 2020). Unlike silica, nonlinear liquids show high nonlinearity that is comparable with the nonlinear soft glasses (Kedenburg et al 2014).…”
Section: Introductionmentioning
confidence: 96%
“…In Refs. [51,52] we proposed PCFs infiltrated with carbon tetrachloride, whereas in Ref. [53] with chloroform.…”
Section: Dispersion and Its Engineering In Pcf Infiltrated With Lmentioning
confidence: 99%
“…In Ref. [51], the proposed PCF consists of eight rings of air-holes ordered in hexagonal lattice. It is made of fused silica glass and the central hole is filled with carbon tetrachloride.…”
Section: Dispersion and Its Engineering In Pcf Infiltrated With Lmentioning
confidence: 99%
See 1 more Smart Citation